Textbook of Craniofacial Growth - Premkumar Sridhar; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2011)
This is a concise book that seeks to provide a (3z(Bone-stop(3y (Bknowledge bank for both undergraduate and post-graduate students, in comprehending craniofacial growth and development. The sway of topics covered is useful not only to students of orthodontics but other specialties as well. Highlights: Basic topics like biology of bone and cartilage, physiology of bone, craniofacial growth and development are covered in a detailed manner for a clear understanding of the micromechanisms involved. The cornucopia of control mechanisms, development of dentition and supporting structures, temporo-mandibular joint, myology, neuromuscular reflexes and maturation of orofacial functions are well illustrated for a thorough knowledge of the stomatognathic system and its far-reaching influence on craniofacial structures. Soft tissue growth and emotional growth are presented, perhaps, for the first time for dental students. Exhaustive reviews of growth in adolescence and beyond, predictions, rotations, patterns in varying skeletal types and how it contributes to stability (or lack) in orthodontic treatment. Can genetics be far behind? Craniofacial anomalies and influence of genetics on growth guides the reader into the world of normal vs subnormal. Plus Factors: (i) A sequential approach of presenting facts, (ii) Extensively researched, (iii) Simple language and illustrations, (iv) Reference listings for further reading, (v) Easy location of key information under specific titles.s
Keywords: Orthodontics and Dentofacial Orthopedics; Electronic books